MODELLING OF PIT LAKE WATER QUALITY DURING THE FILLING STAGE USING RAINFALL AND RIVER WATER - Nisa, Lerian
water, forming a Post-Mining Lake (pit lake). The water quality that develops is greatly influenced by the quality of the leachate from the lithology of the pit wall rocks. Therefore, it is necessary to develop a method for predicting the water quality of post-mining lakes for managing these lakes according to planned success criteria. With accurate predictions, early mitigation measures can be taken to ensure that the water quality of the post-mining lake meets the success criteria, supporting the intended land use for the future. Four rock samples used in this study were taken from pit X at a coal mining company located in East Kalimantan. Two of the rocks characterize as Potentially Acid Forming (PAF), while the other two chategorize as Non Acid Forming (NAF). These four samples represent the rock layers present in the void. This study involves modeling the mixing process in two scenarios: Scenario A, where the void is filled with rainwater, and Scenario B, where the void is filled with both rainwater and river water. To observe the trends in water quality changes, each scenario is divided into four stages. The designed scenario models serve as the basis for mixing simulations. The leachate quality from the kinetic tests of each sample is input as a solution into the PHREEQC software with a mixing volume fraction. The basis for calculating the mixing volume proportion is the filling duration obtained from secondary data. The predicted water quality results for the pit lake show that the chemical and physical characteristics of the water at the end of Scenario B are better than those in Scenario A. In Scenario B, the final pH value is 6.07, while in Scenario A, it is 3.09. The dissolved Fe and Mn concentrations in Scenario A are 11.79 mg/L and 1.31 mg/L, respectively, whereas in Scenario B, the Fe and Mn concentrations are 0.94 mg/L and 0.14 mg/L. The dissolved metal content in Scenario A tends to increase compared to Scenario B, which is more controlled and lower. This difference is due to the larger proportion of river water with good quality in Scenario B, which influences and dominates the neutralization reaction, thereby improving the water quality in a more controlled manner. These results indicate that filling the mining void with river water can accelerate the water improvement process and produce better water quality compared to using rainwater alone.